2017
DOI: 10.5468/ogs.2017.60.3.260
|View full text |Cite
|
Sign up to set email alerts
|

Is massive proteinuria associated with maternal and fetal morbidities in preeclampsia?

Abstract: ObjectiveThe aim of this study was to investigate whether massive proteinuria in preeclampsia is associated with maternal and fetal complications.MethodsWe retrospectively analyzed the clinical records of 233 patients who were diagnosed with preeclampsia. We divided the preeclamptic patients into three groups based on the amount of proteinuria: massive (≥5 g/24 hr), moderate (2 to 5 g/24 hr) and mild (<2 g/24 hr) proteinuria group. We analyzed the clinical characteristics and maternal and neonatal complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
20
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 23 publications
(29 reference statements)
7
20
2
1
Order By: Relevance
“…Mateus et al also showed that massive proteinuria in preeclamptic patients had a negative effect on fetal outcomes in their recent study. They observed a significant decrease in birth weight, birth week and apgar scores [13]. In our study, we also found a significant increase in the duration of stay in neonatal intensive care units in babies of patients with massive proteinuria.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Mateus et al also showed that massive proteinuria in preeclamptic patients had a negative effect on fetal outcomes in their recent study. They observed a significant decrease in birth weight, birth week and apgar scores [13]. In our study, we also found a significant increase in the duration of stay in neonatal intensive care units in babies of patients with massive proteinuria.…”
Section: Discussionsupporting
confidence: 79%
“…The preeclampsia without proteinuria rate is about 10 percent [9]. Many studies showed that high levels of proteinuria were highly related to fetal and maternal morbidity [10][11][12][13]. In our clinic, we did not have any preeclampsia patients without proteinuria on the given dates, so no group was formed as "patients with no proteinuria or patients with proteinuria less than 300 mg. " The reason for that might be the accustomed strong coexistence of preeclampsia with proteinuria in most of the clinicians' minds.…”
Section: Discussionmentioning
confidence: 95%
“…Present study showed a significant association between increased maternal protein in urine and death neonatal outcome (p=0.05). Consistently, Kim et al [24] study in South Korea reported more neonatal morbidities are commonly associated with massive protienurea.Our study showed a significant association between each abnormal maternal renal and liver function tests and dead neonatal outcome. These findings are in agreement with results of Silva Junior et al [25] study in Brazil and Mahajan et al [26] study in India.…”
Section: Discussionsupporting
confidence: 68%
“…Preeclampsia is a complication found in 2-8% of pregnancies and a major cause of maternal and perinatal morbidity and mortality [26][27][28][29][30]. Preeclampsia is a syndrome characterized by deterioration of either the maternal condition (hypertension and proteinuria with or without multiorgan abnormalities) or the fetal condition (intrauterine growth restriction, decreased amniotic fluid) [31][32][33]. Intrauterine growth restriction is a major fetal complication of preeclampsia.…”
Section: Introductionmentioning
confidence: 99%